Consecutive interpreting: An Instructor’s Manual : - Sherwood-Gabrielson, Pam (University of Minnesota, 2008)
This manual is the result of a process that began in 1991 when the first version of this course was offered at the University of Minnesota. In developing and teaching this course, we have relied upon the expertise of many colleagues. We would like to acknowledge the contributions of all the individuals who have worked with us, both directly and indirectly.